Design and Validity of STEM Integrated Physics Electronic Teaching Materials to Improve New Literacy of Class XI High School Students - Annisa N; Asrizal Asrizal (Universitas Muhammadiyah Makassar, 2022)
The 21st century education demands the integration of STEM into learning to improve technology skills, and students' literacy skills can be increased. One of the ways teachers should guide students to face the challenges of the 21st century is by updating the learning resources used. However, in reality schools still use printed teaching materials, have not integrated STEM well, and students' knowledge and literacy are still low. One solution to this problem is to develop STEM-integrated electronic teaching materials (ETMS) to increase new literacy for class XI high school students. This research uses RD method with the Ploom development model. The research carried out is only limited to the development and prototype stages. The analytical technique used is the use of Aiken's V formula. The results of the first study were in the form of an ETMS design. The results of the second study are valid ETMS with an average value of 0.94. Based on the results of the study, two conclusions can be drawn. First, ETMS contains STEM development activities related to the facts of real world problems, technology and working principles, as well as mathematical concepts of physics. Second, the results of the prototype stage consist of self-evaluation and expert review. ETMS is valid based on five indicators of validity assessment, namely material substance, visual communication display, learning design, software utilization, and STEM assessment. This ETMS can be an alternative learning resource to improve students' new literacy.